Peripheral locked in syndrome following snake envenomation – a case report - Gupta, Sweta Kumari; Sarmah, Bhabani Kant; Bajracharya, Amshu Shakya (Journal of College of Medical Sciences-Nepal, 2016)
Snake bite is a terror in the Terai regions of Nepal. It is estimated that at least 20,000 snake bites occur each year with about 1000 deaths in hospitals, mainly in the Terai region. About 25% of the total snake bite cases constitute children in the endemic regions of snakes. Majority of children (85%) following snakebite envenomation develop local or systemic complications. They present in varied ways, from a stable patient with no symptoms to a completely paralyzed child with all features of brain death present, although for a brief time. This has been termed locked in syndrome in snake bite. The locked in syndrome describes patients who are awake and conscious but selectively differenced, i.e., have no means of producing speech, limb or facial movements. If not detected early, it is not uncommon for children presenting with locked in syndrome being put to funeral pyre or buried alive. Sometimes there might not be bite mark making the diagnosis even more challenging. A two year old boy presented with restlessness and quadriparesis following neurotoxic snake envenomation. Later he developed complete paralysis with most features of brain death present like absent dolls eye, absent corneal reflexes and a dilated and fixed pupil only two hours following the bite. He was treated with a standard regimen of anti-snake venom (ASV) along with other supportive measures. His remarkable recovery with the above treatment points towards the necessity of recognizing this syndrome in children following snake bite and continuing all supportive therapies till they regain their reflexes and powers. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 32-34